Temporal Evaluation of Neurosensory Complications After Mandibular Third Molar Extraction: Current Problems for Diagnosis and Treatment - Akashi, Masaya (Open Dent J, 2016)
OBJECTIVE: This retrospective study aimed to report the incidence of neurosensory complications after third molar extraction and also to identify current problems and discuss appropriate management of these complications. METHOD: Patients who underwent extraction of deeply impacted mandibular third molars under general anesthesia were included. The following epidemiological data were retrospectively gathered from medical charts: type of neurosensory complication, treatment for complication, and outcome. RESULTS: A total 369 mandibular third molars were extracted in 210 patients under general anesthesia during this study period. Thirty-one of the 369 teeth (8.4%) in 31 patients had neurosensory complications during the first postoperative week resulting from inferior alveolar nerve damage. Neurosensory complications lasting from 1 to 3 months postoperatively included 17 cases of hypoesthesia and 8 of dysesthesia in 19 patients. Five cases of hypoesthesia and 4 of dysesthesia in 5 patients persisted over 1 year postoperatively. Sixteen of 369 teeth (4.3%) in 16 patients had persistent neurosensory complications after third molar extraction under general anesthesia. Stellate ganglion block was performed in 4 patients. Early initiation of stellate ganglion block (within 2 weeks postoperatively) produced better outcomes than late stellate ganglion block (over 6 months postoperatively). CONCLUSION: Refractory neurosensory complications after third molar extraction often combine both hypoesthesia and dysesthesia. Current problems in diagnosis and treatment included delayed detection of dysesthesia and the lack of uniform timing of stellate ganglion block. In the future, routinely inquiring about dysesthesia and promptly providing affected patients with information about stellate ganglion block might produce better outcomes.